Direct and indirect effects of conjugated estrogens/bazedoxifene treatment on quality of life in postmenopausal women. (December 2016) - Abraham, Lucy; Bushmakin, Andrew G.; Dragon, Erika; Komm, Barry S.; Pinkerton, JoAnn V.
Highlights: CE/BZA indirectly improved MENQOL vasomotor domain by minimizing HFs. CE/BZA also improved MENQOL vasomotor domain directly. HF severity had a greater impact on all MENQOL domains than HF frequency. Degree of HF severity is a relevant target when treating symptomatic menopausal women. Abstract: Objective: Determine the direct and indirect effects of conjugated estrogens/bazedoxifene (CE/BZA) treatment on menopause-specific quality of life in a post-hoc analysis of 2 phase 3 Selective estrogens, Menopause, And Response to Therapy (SMART-1, SMART-2) trials. Study design: Data from participants in SMART-1 and SMART-2 who received CE 0.45 mg/BZA 20 mg, CE 0.625 mg/BZA 20 mg, or placebo were analyzed, including week 12 data from 1274 healthy postmenopausal women in SMART-1 and pooled week 1–4 and 9–12 data from 332 women with moderate to severe vasomotor symptoms (≥7 HFs/d or ≥50/wk) in SMART-2. Main outcome measures: A statistical mediation model included treatment as a binary predictor variable (pooled active treatment vs placebo), Menopause-Specific Quality of Life (MENQOL) questionnaire domains (vasomotor, sexual, psychosocial, and physical function) as the outcomes variables, and frequency/severity of hot flushes (HFs) as treatment effect mediators on MENQOL. Results: Vasomotor function was affected directly (SMART-1: 35.8%, P  < 0.05; SMART-2: 48.7%, P  < 0.05)] by CE/BZA and indirectly through improvements in HF severity (57.0%, P  < 0.05; 42.1%, P  < 0.05), and to a lesser extent, through reduction in HF frequency (7.2%, P  < 0.05; 9.2%, P  < 0.05). The effects of CE/BZA on the sexual, psychosocial, and physical function domains were fully mediated via improvements in HF severity. Final models for both studies were similar, indicating that direct and indirect effects of CE/BZA on menopause-specific quality of life are consistent and stable in different samples of women. Conclusions: CE/BZA affected the MENQOL vasomotor domain both directly and indirectly, whereas effects on other domains were fully mediated via HF severity reductions.